"Healing on Both Sides": Strengthening the Effectiveness of Prison–Indigenous Community Partnerships Through Reciprocity and Investment - Varcoe, Colleen; Brown, Helen; Timler, Kelsey; Taylor, Melissa; Straus, Elizabeth (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2020)
This mixed methods study examined the impact of a prison–community partnership, entitled Work 2 Give. The partnership supports a program in which federally incarcerated men in Canada make items to donate to Indigenous communities. Qualitative interviews were conducted with participating men (n = 32), recipient community members (n = 29), and other prison and community stakeholders (n = 14). Selected outcomes (transfers to higher security, successful transfers to lower security, and serious institutional charges) were examined for 60 incarcerated men for whom data were available. Findings suggest that the program positively affected the men’s identities and provided opportunities for communities to help incarcerated men to heal; both sets of stakeholders see potential to strengthen the program. Whereas the emphasis has been on unidirectional donation, and the impetus for the program has been with correctional staff, findings suggest a bidirectional model with stronger feedback loops between the prison and community to support reciprocity, investment, and visibility would enhance impact. This model has broad implications for strengthening community–prison partnerships.